Enhancing H11 Protein-Induced Immune Protection Against Haemonchus contortus in Goats: A Nano-Adjuvant Formulation Strategy - Lisha Ye; Simin Wu; Fuqiang Liu; Juan Zhang; Jie Wan; Chunqun Wang; Hui Liu; Min Hu (Biology)
The only vaccine against Haemonchus contortus is limited by short-lived antibody persistence and the need for frequent booster immunizations. This study leveraged the advantages of nano-adjuvants in enhancing antigen presentation and immune regulation to evaluate the efficacy of novel adjuvants (IMX, AddaS03) and the conventional QuilA combined with H11 protein. Goats were divided into four groups (IMX + H11, AddaS03 + H11, QuilA + H11, and infected control). They were immunized three times and challenged with 6000 infective third-stage larvae (iL3s) of H. contortus on the day of the third immunization, with the experiment lasting for 98 days. The results showed that vaccination with IMX + H11 conferred the strongest protection, demonstrating 88.3% efficacy in fecal egg count (FEC) reduction and 75.8% efficacy against worm burden, followed by QuilA + H11 (85.2% FEC reduction and 68% worm burden reduction) and AddaS03 + H11 (79.4% FEC reduction and 61.3% worm burden reduction). Serum IgG analysis revealed high antibody levels in all immunized groups. Cytokine detection found that IMX + H11 significantly upregulated IL-2 and IFN-γ expression in PBMCs and TNF-α expression in splenocytes, activating Th1-type responses and immune memory. QuilA + H11 showed weaker Th1 activation, and AddaS03 + H11 faced limitations due to insufficient antibody persistence for long-term protection. These findings suggest that IMX can induce highly efficient humoral and cellular immunity, providing a new direction for the optimization of H. contortus vaccines and suggesting the importance of nano-adjuvants for precise regulation of immune patterns.